Development of the New Generation of Clamping Jaws for Thermomechanical Simulator - Kalina, Tomas; Marek, Vaclav (Manufacturing Technology Journal, 2019)
This paper presents a development and design of new multifunctional clamping jaws for thermomechanical simulator. In the article there is presented what the thermomechanical simulator is and what is it used for. The article also describes the requirements for the thermomechanical simulator jaws and how they were achieved. All important parts of which the thermomechanical simulator jaws are assembled and used are described in detail. Finally, thermal simulations of the jaws were performed under operating loads. This technical solution is protected as a utility model registered on The Industrial Property Office - Czech Republic.
Keywords: Clamping jaws; thermomechanical simulator; heat treatment; forged parts